Children’s Safety Education Model through Child-Friendly Games - Widowati, Evi; Hendriyani, Rulita; Nugroho, Efa; Qin, Axel Lee Wye (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Children are vulnerable to potential hazards from their environment because of theircognitive, psychological and social developments are in immature stages. Formal educationis still lacking in teaching safety concepts for children, hence a fun educationalmedia for children is needed so that children can learn through child-friendly educativegames. Because of that develop a fun child safety education model is important toimprove childrenÃ¢â‚¬â„¢s knowledge on the importance of safety, so that children can easilyunderstand how to implement safety values in their life. We used Research and Development(R&D) level 1 design to develop childrenÃ¢â‚¬â„¢s safety education game, which consistedof five stages, started from the data collection up to assess the product effectiveness. Theresult was a Ã¢â‚¬Å“snake and ladders of safetyÃ¢â‚¬Â game as safety education media for children.We presented 12 pictures in Ã¢â‚¬Å“snake and ladders of safetyÃ¢â‚¬Â game. This research was conductedon year 2017. Based on the game evaluation, the highest average pretest scorewas 37.9 and the average posttest score increased to 65.5, hence there was an increase ofknowledge on safety by 73.1%. It can be concluded that this game can increase childrenÃ¢â‚¬â„¢sknowledge on safety.